EFFECTIVENESS OF STAGEN USE ON DECREASED UTERINE FUNDUS - Umaroh; Musdalifah, Ulfa; O, Dhita Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of Sustainable Development Goals (SDGs) 2030 guarantees healthy life and promotes welfare for all people at all ages. The decrease in number is not in accordance with the target SDGs. Three causes of maternal death in Indonesia are bleeding, hypertension in pregnancy (HDK), and infection. (Indonesian Ministry of Health, 2015). Alternative efforts to use stagen to increase uterine contractions in post-partum mothers. The purpose of this study was to determine of stagen in reducing uterine fundus between 5 meters, 10 meters and the effectiveness of using traditional blinding to prevent bleeding that often occurs during the post-partum period. This type of experimental research, Quasi-research methods experimental with time series control group. Data analysis Repeated Measures Anova. The population of post-partum in Central Java, Samples of 20 postpartum mothers in the 5 meter and 38 in the 10 meter stagen group, 20 in the traditional blinding group. Data collection by measuring the height of the fundus uteri at 1, 3, 5 and 7 day’s post-partum. The instruments used were metlin and measurements with ultrasound on the 7th day post-partum. Results of the study of the decrease in TFU with mean in the TFU traditional blinding group on day 1 to day 7 were 5,550 cm, while on day 7 with day 3 4,075 cm and day 7 with fifth day was 1,675 cm. with a value of P 0,000 which means meaningful. In the 5 meter stagen group results were obtained, TFU on day 1 with day 7 means 5,289, day 7 with day 3 mean 3,605 while on day 7 with day 5 with mean 1,711. with a value of P 0,000 which means meaningful. In the 10 meter stagen group the results were obtained, TFU on day 1 with day 7 means 6,658, day 7 with day 3 mean 3,605 while on day 7 with day 5 with mean 0,505. with a value of P 0,000 which means meaningful. Conclusion 10 meters of stagen is most effective with an average decrease in TFU on day 7 of 6.658 cm. Suggested normal labor can use 10 meters of stagen so that uterine contractions can run normally.